Plantas medicinais como um recurso popular de utilização na saúde da mulher: uma revisão integrativa de literatura - SANTOS, Síria Daniela Macambira (Universidade Federal do Oeste do Pará, 2024)
The medicinal plants are the plant species itself capable of being used for therapeutic purposes. The use of traditional medicine in women's health care becomes an important means of treatment and prevention in the Amazonian context. Given the above, the present study has the general objective of understanding the factors related to the use of medicinal plants by women in the Amazon; and, as specific objectives: identify the plants used for medicinal purposes by women in their health care and know the indications for treatment, use and preparation of plants used for medicinal purposes in women's health. The present work consists of an integrative literature review (ILR). The bibliographic survey was carried out in electronic databases such as: Google Scholar; Online Scientific Electronic Library - SciELO and Latin American and Caribbean Health Sciences Literature - LILACS, Medical Literature Analysis and Retrieval System Online - MEDLINE and National Library of Medicine - NLM/PUBMED. The selection also took place through titles and descriptors with combinations of isolated keywords or in conjunction. The total of works found from the selected descriptors was 54313 publications and at the end of the selection and application of the exclusion and inclusion criteria, of the 64 academic works that served as the basis for the present review, 11 works were arranged in a table for further discussion. The survey of medicinal plants used by women in the care of their health, correspond to treatment indications such as: menstrual disorders, corresponding to 38.8%, followed by 25.9% for uterine inflammations and 22.2% for venereal diseases. It was observed that even with the implementation of policies aimed at women's comprehensive health, women are still seen from a reductionist perspective of wife, mother and housewife. The study showed the need for more work carried out in the Amazon region, since the region is rich in its biodiversity, but lacking in income and quality health service; as well as studies that identify the social determinants in health for the use of medicinal plants in the health of amazonian women.